Neuroimmunoendocrine Link Between Chronic Kidney Disease and Olfactory Deficits - Corona, Rebeca; Ordaz, Benito; Robles-Osorio, Ludivina; Sabath, Ernesto; Morales, Teresa (Frontiers in Integrative Neuroscience, 2022)
Chronic kidney disease (CKD) is a multifactorial pathology that progressively leads to the deterioration of metabolic functions and results from deficient glomerular filtration and electrolyte imbalance. Its economic impact on public health is challenging. Mexico has a high prevalence of CKD that is strongly associated with some of the most common metabolic disorders like diabetes and hypertension. The gradual loss of kidney functions provokes an inflammatory state and endocrine alterations affecting several systems. High serum levels of prolactin have been associated with CKD progression, inflammation, and olfactory function. Also, the nutritional status is altered due to impaired renal function. The decrease in calorie and protein intake is often accompanied by malnutrition, which can be severe at advanced stages of the disease. Nutrition and olfactory functioning are closely interconnected, and CKD patients often complain of olfactory deficits, which ultimately can lead to deficient food intake. CKD patients present a wide range of deficits in olfaction like odor discrimination, identification, and detection threshold. The chronic inflammatory status in CKD damages the olfactory epithelium leading to deficiencies in the chemical detection of odor molecules. Additionally, the decline in cognitive functioning impairs the capacity of odor differentiation. It is not clear whether peritoneal dialysis and hemodialysis improve the olfactory deficits, but renal transplants have a strong positive effect. In the present review, we discuss whether the olfactory deficiencies caused by CKD are the result of the induced inflammatory state, the hyperprolactinemia, or a combination of both.